PENGARUH MOTIVASI KERJA DAN FAKTOR LAINNYA TERHADAP DISIPLIN KERJA CV. SBE - Sari, Mella Melinda; Ananda, Denta Felli (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to analyze and determine the effect of work motivation, leadership style, and work environment on the work discipline of employees of CV. SBE. The population used in this study were 58 employees using a purposive sampling technique.This sampling technique involves 50 permanent employees of CV. SBE. Data collection techniques through distributing questionnaires using a Likert scale. The analytical method of this study uses linear regression. Based on the results of hypothesis testing data analysis in this study, it shows that work motivation has no effect on work discipline, leadership style has an effect on work discipline, and the work environment has no effect on employee work discipline.